Methodological issues in online data collection - Cantrell, Mary Ann; Lupinacci, Paul (Journal of advanced nursing, 2007)
Title.  Methodological issues in online data collection Aim.  This paper is a report of a study to evaluate the use of an online data collection method to survey early survivors of childhood cancer about their physical and psychosocial characteristics and health‐related quality of life. Background.  A major advantage in conducting web‐based nursing research is the ability to involve participants who are challenging to study because of their small numbers or inaccessibility because of geographic location. As paediatric oncology patients and early survivors of childhood cancer are often not easily accessible because of their small numbers at single institutions, web‐based research methods have been proposed as a potentially effective approach to collect data in studies involving these clinical populations. Method.  Guided by published literature on using the Internet for data collection, an online protocol was developed; this included construction of a website, development of a homepage and interactive HyperText Markup Language pages and the posting of the study link on various websites. Data collection occurred over a 6‐month period between December 2005 and May 2006. Findings.  Despite using strategies in conducting online research cited in published literature, the recruitment of subjects was very prolonged and the volume of missing data among many respondents excluded them from the study and created bias within the study’s results. Conclusion.  Web‐based, online data collection methods create opportunities to conduct research globally, especially among difficult to access populations. However, web‐based research requires careful consideration of how the study will be advertized and how data will be collected to ensure high quality data and validity of the findings.